THE EFFECT OF USING DIRECTED READING THINKING ACTIVITY (DRTA) STRATEGY TOWARD STUDENTS’ READING COMPREHENSION OF NARRATIVE TEXT AT EIGHTH GRADE STUDENTS OF MTSN 9 PADANG PARIAMAN - Antonio, Rayhan; Syahrul, Syahrul; Syafitri, Widya; Lismay, Leli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was grounded in the problems encountered by eighth-grade students in comprehending narrative texts. These problems included difficulties in making predictions, limited vocabulary mastery, and low learning motivation, which consequently led to passive reading and the lack of activation of prior knowledge. Such conditions highlighted the need for an appropriate instructional strategy; therefore, the Directed Reading Thinking Activity (DRTA) strategy was implemented to promote active reading, prediction, and critical thinking. This study aimed to determine the effect of the DRTA strategy on students’ reading comprehension. A quantitative approach with a quasi-experimental design was employed. The population was all eighth-grade students of MTsN 9 Padang Pariaman, and the sample was determined by using cluster random sampling. The instrument was a reading comprehension test in the form of multiple-choice questions administered in pre-test and post-test. The results showed that the DRTA strategy had a significant effect on students’ reading comprehension, as students taught using DRTA achieved better results than those taught using conventional methods. In addition, the implementation of DRTA increased students’ participation, motivation, and engagement in the learning process.